Fake Coronavirus Pandemic is Biggest Scam and Crimes against Humanity - Version 1_Redacted - RAKHESH JAGHADISH L (RAKHESH JAGHADISH L, 2023)
CORONAVIRUS SCAM – COVID-19 DOES NOT EXIST; THIS IS A PRE-PLANNED BOGUS PANDEMIC AND THE BIGGEST SCAM IN THE HUMAN HISTORY Sinful acts and unforgivable sins against Nature, humanity, science, country, and its constitution Rakhesh Jaghadish L THE REPORT – Version 1 – February 22, 2023 Atrocities and mass murders against Nature's human beings on this earth Date – 23 February 2023 Coronavirus or COVID-19 pandemic virus does not exist naturally. This coronavirus COVID-19 pandemic is bogus, and the lies of the Inhumans, such as the criminal elites, governments, media, pharmaceutical companies, etc. To humankind, to the People of all Countries, human rights organizations, independent activists, human rights defenders, & all the Justice Department of the Country:⸺ “Afghanistan, Albania, Algeria, Andorra, Angola, Antigua and Barbuda, Argentina, Armenia, Austria, Azerbaijan, Bahrain, Bangladesh, Barbados, Belarus, Belgium, Belize, Benin, Bhutan, Bolivia, Bosnia and Herzegovina, Botswana, Brazil, Brunei, Bulgaria, Burkina Faso, Burundi, Cabo Verde, Cambodia, Cameroon, Canada, Central African Republic, Chad, Channel Islands, Chile, China, Colombia, Comoros, Congo, Costa Rica, Côte d'Ivoire, Croatia, Cuba, Cyprus, Czech Republic, Denmark, Djibouti, Dominica, Dominican Republic, DR Congo, Ecuador, Egypt, El Salvador, Equatorial Guinea, Eritrea, Estonia, Eswatini, Ethiopia, Faeroe Islands, Finland, France, French Guiana, Gabon, Gambia, Georgia, Germany, Ghana, Gibraltar, Greece, Grenada, Guatemala, Guinea, Guinea-Bissau, Guyana, Haiti, Holy See, Honduras, Hong Kong, Hungary, Iceland, India, Indonesia, Iran, Iraq, Ireland, Isle of Man, Israel, Italy, Jamaica, Japan, Jordan, Kazakhstan, Kenya, Kuwait, Kyrgyzstan, Laos, Latvia, Lebanon, Lesotho, Liberia, Libya, Liechtenstein, Lithuania, Luxembourg, Macao, Madagascar, Malawi, Malaysia, Maldives, Mali, Malta, Mauritania, Mauritius, Mayotte, Mexico, Moldova, Monaco, Mongolia, Montenegro, Morocco, Mozambique, Myanmar, Namibia, Nepal, Netherlands, Nicaragua, Niger, Nigeria, North ...